Strengthening the link between organizational culture and employee loyalty: Exploring the mediating effects of employee trust and job satisfaction - Pham Hoang Hien; Tran Thanh Tuan (Global Business & Finance Review (GBFR), 2023)
Purpose: This research investigates the role of employee trust and job satisfaction in the relationship between organizational culture and employee loyalty. Design/methodology/approach: The study was conducted among 355 healthcare professionals working in a private healthcare system in southern cities of Vietnam, including doctors, nurses, and other medical staff. The research method employed was partial least squared structure equation modeling (PLS-SEM) with SmartPLS software for data analysis. Findings: The findings indicate that organizational culture has a direct positive impact on employee loyalty and also affects employee trust and job satisfaction positively. Furthermore, employee trust and job satisfaction act as intermediaries and positively influence employee loyalty toward the organization. Research limitations/implications: The research acknowledges the limitation of the limited sample size and encourages further exploration of these relationships in other contexts. In addition, this study provides valuable insights for the management board of private healthcare organizations in southern cities of Vietnam on how to improve employee loyalty by cultivating a positive organizational culture, promoting employee trust, and enhancing job satisfaction. Originality/value: Overall, this research contributes significantly to the existing literature by examining the interplay between employee trust, organizational culture, job satisfaction, and employee loyalty.
Keywords: 650; Employee loyalty; Employee trust; Organizational Culture; Employee job satisfaction; The private healthcare sector